A study on FVSI index as an indicator for Under Voltage Load Shedding (UVLS) - Ramasamy A.; Verayiah R.; Zainal Abidin H.I.; Musirin I. (2023)
In the time of rapid growth, there is an increase of demand for a reliable and stable power supply. Power utilities are pressured to cater the rising demand with the existing system. Thus, monitoring the voltage stability of the system has become crucial. Under Voltage Load Shedding (UVLS) is one of the many methods that are used to sustain voltage stability. On the other hand, Fast Voltage Stability Index (FVSI) index is proven to be a good indicator for voltage stability in a system. This paper will study on the correlation between FVSI index and UVLS scheme. From the simulation, the results clearly indicate that FVSI index can be used to indentify location to be load shed. 2009 IEEE.